Development of Trigona SP (Stingless Bee) Honey Bee Cultivation as an Alternative Economy in Urban Community (Urban Bee) at Kelurahan Kampung Baru Kecamatan Medan Maimun - Rafida Khairani; Rahmat Alamsyah Harahap; Kristi Endah Ndolisa Ginting; Afriza Amir; Khana Saputri; Jarunjung Hutagaol (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Increasing public awareness about the great benefits contained in honey has created new business fields for new producers and even old producers. Unstable economic conditions of course make everyone must have skills that can make additional sources of income a source of basic income if at any time laid off from work. This Community Service teaches the importance of honey and how to manage it so that it can be managed by the community in the yard so that it can become a source of income. people can receive information well so that it becomes knowledge and increases their skills.